The effectiveness of assistance provided by the department of agriculture, food, and fisheries in enhancing fishermen’s empowerment in Pariaman City - Habib Alghiffari; Intan Slipilia (Priviet Social Sciences Journal, 2026)
This study examines the effectiveness of assistance provided by the Department of Agriculture, Food, and Fisheries of Pariaman City in enhancing fisherfolk empowerment. Fishermen in coastal areas face various challenges, including limited access to modern fishing gear, fluctuating fish prices, and environmental uncertainties that affect productivity and welfare. Government assistance programs are expected to address these issues by strengthening the capacity, independence, and economic resilience of the fishermen. This study employed a qualitative descriptive design. Data were collected through observations, in-depth interviews, and documentation involving key informants from the Department of Agriculture, Food, and Fisheries, Fisheries Extension Officers, community representatives, and fishermen in Pariaman City. Data analysis was conducted using Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion-drawing. The findings indicate that assistance programs have generally been effective in improving fisher empowerment. Assistance in the form of fishing gear and supporting facilities has contributed to increased fishing activity, improved catch efficiency, and reduced operational costs of fishing. In addition, training and mentoring activities have enhanced fishermen’s knowledge, skills, and awareness of sustainable marine-resource management. However, the effectiveness of the assistance has not been fully optimal because of uneven distribution, limited participation of fishermen in program planning, and insufficient program adaptation to diverse socio-economic conditions. Overall, the study concludes that the assistance provided has a positive impact on fishermen’s empowerment in Pariaman City, although improvements in participation, integration, and sustainability are necessary to achieve long-term empowerment of the fisher community.